2019
DOI: 10.1186/s12969-019-0308-7
|View full text |Cite
|
Sign up to set email alerts
|

The pediatric rheumatology objective structured clinical examination: progressing from a homegrown effort toward a reliable and valid national formative assessment

Abstract: BackgroundOf 37 pediatric rheumatology fellowship training programs in the United States, many have three or fewer fellows at a given time, making large-scale assessment of fellow performance difficult. An objective structured clinical examination (OSCE) is a scenario-based simulation method that assesses individual performance, thus indirectly measuring training program effectiveness. This study describes the development and implementation of two national pediatric rheumatology OSCEs and methods used for prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The toolbox suggests assessment methods, including the use of anatomic models, direct observation, objective structured clinical examinations, and faculty evaluations, some of which have feasibility or validity data for rheumatology trainees. [38][39][40][41] Of note, few publicly-available assessment forms exist, and none are directly included in the toolbox. Examples of published curricula with assessment tools include the Fellow as Clinical Teacher curriculum and a workshop to measure performance of knee and shoulder arthrocentesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The toolbox suggests assessment methods, including the use of anatomic models, direct observation, objective structured clinical examinations, and faculty evaluations, some of which have feasibility or validity data for rheumatology trainees. [38][39][40][41] Of note, few publicly-available assessment forms exist, and none are directly included in the toolbox. Examples of published curricula with assessment tools include the Fellow as Clinical Teacher curriculum and a workshop to measure performance of knee and shoulder arthrocentesis.…”
Section: Discussionmentioning
confidence: 99%
“…No analogous curricular document exists for pediatric rheumatology. The toolbox suggests assessment methods, including the use of anatomic models, direct observation, objective structured clinical examinations, and faculty evaluations, some of which have feasibility or validity data for rheumatology trainees 38–41 . Of note, few publicly‐available assessment forms exist, and none are directly included in the toolbox.…”
Section: Introductionmentioning
confidence: 99%
“…Megan Curran and David Sherry have been involved in developing and testing the objective structured clinical exams (OSCE) for pediatric rheumatology fellows to evaluate their communication and professionalism skills. 14 A pre-test and post-test design was used to evaluate the fellows’ change in skills. The study results showed that there was improvement in post-test scores as well as professionalism after training using the OSCE.…”
Section: Discussionmentioning
confidence: 99%
“…2224 Therefore, additional and ongoing educational interventions are needed at the level of the HCPs, other pediatric providers as well as the community, patients and caregivers; however, a more methodologically sound evaluation is needed. We will consider holding pediatric rheumatology objective structured clinical examination sessions (OSCE), a scenario-based simulation method that assesses individual performance, 25 and case-based education to HCPs throughout the state. A randomized control trial of educational interventions can provide true measures of knowledge gain rather than perceptions of knowledge gain.…”
Section: Discussionmentioning
confidence: 99%